Answer:
- 6x² - 2x + 1
Step-by-step explanation:
Given
(2x³ - 4x² - 3x + 5) + (- 2x³ - 2x² + x - 4)
Both parenthesis are distributed by 1 thus just remove them
= 2x³ - 4x² - 3x + 5 - 2x³ - 2x² + x - 4 ← collect like terms
= - 6x² - 2x + 1
$0.05(n) + $0.10(d) = $1.90
n + d = 27
n + d - d =27 - d
n = 27 - d
$0.05(27-d) + $0.10(d) = $1.90
1.35 - 0.05d + 0.10d = $1.90
1.35 +0.05d = $1.90
1.35 - 1.35 +0.05d = $1.90 -1.35
0.05d = 0.55
0.05d/0.05 = 0.55/0.05
d = 11
n = 27 - 11
n = 16
$0.05(16) + $0.10(11) = $1.90
$0.80 + $1.10 = $1.90
$1.90 = $1.90
Answer: y = -5
Substitute in 3 for x.
x - y = 8 Substitution
3 - y = 8 Subtract 3 from both sides
-y = 5 Divide by -1 to both sides
y = -5 Answer!
You can also check your work.
x - y = 8
3 - (-5) = 8
3 + 5 = 8
8 = 8
Answer:
I believe its 42
Step-by-step explanation:
i did n =14 i think and then multiplied it by 3 but i really dont exactly know
Answer:
just x both together
Step-by-step explanation: